The importance's of the physical analogue clock in mediating learning of analogue clock time in Grade 4 learners - Metelerkamp, Roger Gregory (Rhodes University, Faculty of Education, Department of Education, 2014)
My research topic concerns how learners use the analogue clock (as a human tool) to make meaning of clock time. This study is informed by a Vygotskian socio-cultural framework to learning and development based on the concept that human activities take place in cultural contexts and is mediated by tools. In this qualitative study I report on the learners meaning making of analogue clock time using the physical clock. This study was carried out at a South African primary school through an intervention programme after school. The research employed a case study method. It involved a purposeful sample of 4 learners (n=38) from the grade four class group based on their response to a baseline assessment task. The selected sample of learners included learners across the ability spectrum to gain rich insight into how learners make meaning of analogue clock time. Data collection and analysis was done through an interpretive approach. The video-taped interviews and intervention programme was my main instrument of data collection. Other research instruments included document analysis of responses to baseline assessment tasks. These research tools yielded the data collected and also allowed for triangulation. My research topic explored how the learners make meaning of analogue clock time. In particular the two-way movement of how the learners use the physical tool namely the analogue clock to develop meaning and how the clock mediates clock knowledge in return. The findings of the study suggest that learners' find it difficult to conceptualise analogue clock symbols and signs, in particular, in Afrikaans the half hour concept, in relation to the two hands. The physical analogue clock is also important to support and extend clock knowledge in solving time-related problems. This shows the power of the analogue clock to mediate meaning making of clock time in young learners. Because of its potential to improve teaching and learning analogue clock time in primary school it is therefore recommended that the analogue clock time be further researched in South Africa.
Keywords: Clocks and watches; Mathematics -- Study and teaching (Elementary); Time measurements -- Study and teaching (Elementary)